A c‐fos‐Monomeric Red Fluorescent Protein 1 Fusion Transgene is Differentially Expressed in Rat Forebrain and Brainstem after Chronic Dehydration and Rehydration. (12th April 2013) - Yoshimura, M.; Ohkubo, J.; Katoh, A.; Ohno, M.; Ishikura, T.; Kakuma, T.; Yoshimatsu, H.; Murphy, D.; Ueta, Y.
<x xml:space="preserve">Abstract</x> We have previously shown that an acute osmotic stimulation induces the expression of a c‐fos and monomeric red fluorescent protein 1 (mRFP1) fusion transgene in osmosensitive rat brain areas, including the supraoptic (SON) and paraventricular nuclei (PVN). However, the effects of chronic stimuli, such as dehydration, have not been investigated. In the present study, the expression patterns of the c‐fos‐mRFP1 fusion gene in the forebrain and the brainstem of male and female transgenic rats were studied in seven experimental groups: ad lib. water (euhydration), water deprivation for 12, 24 or 48 h (dehydration) and water deprivation for 46 h + ad lib. water for 2, 6 or 12 h (rehydration). The number of cells that express nuclear mRFP1 fluorescence was quantified in the hypothalamus, the circumventricular organs and the brainstem. Compared to the euhydrated state, the number of transgene expressing cells significantly increased in all forebrain areas and in the rostral ventrolateral medulla after dehydration and 2 h of rehydration. In the nucleus of the solitary tract and area postrema, the number of mRFP1 fluorescent cells was markedly increased after 2 h of rehydration. Although the number of mRFP1 fluorescent cells in the organum vasculosum laminae terminalis, median preoptic nucleus and subfornical organ remained significantly increased after 6 h of rehydration, reaching control levels after 12 h of rehydration, the number of mRFP1 fluorescent cells in the SON and the PVN reached control levels after 6 h of rehydration. There were no significant differences between male and female rats. These results show that the expression of the c‐fos‐mRFP1 fusion gene changes in the forebrain and the brainstem not only after acute osmotic stimulation, but also after chronic osmotic stimulation. Interestingly, these studies reveal the differential activation of different neuronal groups over the time course of dehydration and rehydration.